Formation, Energetics, and Electronic Properties of Graphene Monolayer and Bilayer Doped with Heteroatoms - Yoshitaka Fujimoto (Advances in Condensed Matter Physics)
Doping with heteroatoms is one of the most effective methods to tailor the electronic properties of carbon nanomaterials such as graphene and carbon nanotubes, and such nanomaterials doped with heteroatom dopants might therefore provide not only new physical and chemical properties but also novel nanoelectronics/optoelectronics device applications. The boron and nitrogen are neighboring elements to carbon in the periodic table, and they are considered to be good dopants for carbon nanomaterials. We here review the recent work of boron and nitrogen doping effects into graphene monolayer as well as bilayer on the basis of the first-principles electronic structure calculations in the framework of the density-functional theory. We show the energetics and the electronic properties of boron and nitrogen defects in graphene monolayer and bilayer. As for the nitrogen doping, we further discuss the stabilities, the growth processes, and the electronic properties associated with the plausible nitrogen defect formation in graphene which is suggested by experimental observations.